Hubungan Self-Directed Learning dengan prokrastinasi akademik dan jumlah target hafalan - Sabrina, Farah; Mardhiyah, Zahrina (TA`DIBUNA, 2024)
One of the factors of academic procrastination is self-directed learning (SDL), namely the individual's ability to build initiative and be responsible for the learning they have chosen. This research is a cross-sectional study, aiming to determine the relationship between SDL and academic procrastination in memorizing the Al-Quran with a quantitative approach using cluster random sampling on 94 class XII female students. Data collection used a Likert scale for academic procrastination (α 0.897; 32 items) and SDL (α 0.802; 13 items). The results of the research show that there is a relatively strong relationship between academic procrastination and self-directed learning (p 0.000<0.05; rxy -0.665), which means that the higher the SDL, the lower the level of academic procrastination. Vice versa. Self-directed learning can encourage individuals to become more motivated, and skilled at managing and evaluating themselves so that it tends to minimize the emergence of academic procrastination. This research implies that students can think critically, and independently in developing and implementing appropriate learning strategies, are disciplined, and are enthusiastic about showing their best academic achievements.   Abstrak Salah satu faktor prokrastinasi akademik adalah self-directed learning (SDL), yaitu kemampuan individu untuk membangun inisiatif dan bertanggungjawab atas pembelajaran yang telah dipilihnya. Penelitian ini merupakan cross sectional study, bertujuan untuk mengetahui hubungan antara SDL dengan prokrastinasi akademik hafalan Al-Quran dengan pendekatan kuantitatif menggunakan cluster random sampling pada 94 siswi kelas XII. Pengumpulan data menggunakan skala Likert untuk prokrastinasi akademik (α 0.897; 32 items) dan SDL (α 0.802; 13 items). Hasil penelitian menunjukkan bahwa terdapat hubungan dengan kekuatan yang tergolong kuat antara prokrastinasi akademik dengan self-directed learning (p 0.000<0.05; rxy -0.665), yang berarti bahwa semakin tinggi SDL maka semakin rendah tingkat prokrastinasi akademiknya. Begitu pun sebaliknya. Self-directed learning mampu mendorong individu menjadi lebih termotivasi, terampil mengelola dan evaluasi diri sehingga cenderung meminimalisasi munculnya prokrastinasi akademik. Implikasi penelitian ini adalah siswa mampu berpikir kritis, mandiri dalam menyusun dan menerapkan strategi belajar yang tepat, disiplin, serta bersemangat menunjukkan prestasi akademik terbaiknya.